CARBON EMISSION DISCLOSURE IN INDONESIA: THE EFFECT OF PROFITABILITY AND LEVERAGE ON COAL SUB-SECTOR - Nurrohmah, Alya Atifa; Ambarwanti, Novia Setyo (Jurnal Pijar, 2024)
This study aims to examine the effect of profitability and leverage on carbon emission disclosure (CED) in coal sub-sector mining companies in the 2021-2022 period. The population in this study amounted to 30 companies. The sampling technique used purposive sampling so as to get 18 sample companies with 36 observations. This research is a quantitative research using secondary data and tested with the method adopted from the check list obtained from the Carbon Disclosure Project (CDP). The results showed that the profitability variable and the leverage variable had no effect and were not significant to the disclosure of carbon emissions.